Model Pengembangan Kelembagaan Pembentukan Wilayah Kesatuan Pengelolaan Hutan di Provinsi Papua - K Karsudi; Rinekso Soekmadi; Hariadi Kartodihardjo (Jurnal Manajemen Hutan Tropika, 2010)
The implementation of forestry policy in Papua Province has not been significantly optimal as indicated by the high poverty rate around and within the region and the increasing rate of forest degradation. To overcome the problems of the forestry sector, a policy is introduced in the form of Kesatuan Pengelolaan Hutan (KPH) or Forest Management Units. This policy is an enabling condition for the realization of sustainable forest resources and community welfare. The success of KPH is largely determined by the capacity of local stakeholders that includes understanding, coordination and cooperation, and readiness of the organizations that manage KPH.  Therefore, this research was conducted to design an institutional model of establishing the region of KPH and formulate organizational structure of KPH. The study was conducted in Jayapura of Papua Province and Regency of Yapen Islands by the use of purposive sampling method for data/information collecting and decision-making tool of Analytical Hierarchy Process (AHP) for data analyzing, which was then analyzed descriptively. The results showed that the performance in establishing the KPH regions in Papua Province was at the medium level of achievement or approximately 29.50% of the criteria and indicators for the formation of KPH regions. This condition was considered low as result of the poor understanding and ineffective cooperative relationships and coordination among stakeholders. Thus, the formulation of the institutional model should be directed to increase the role, capacity, and effectiveness of stakeholder relations. Regarding to the findings, a state owned enterprise is viewed as highly feasible to manage KPH in Papua Province.